Securing a Supramolecular Architecture by Tying a Stopper Knot. Issue 33 (27th May 2018) - Leigh, David A.; Pirvu, Lucian; Schaufelberger, Fredrik; Tetlow, Daniel J.; Zhang, Liang
Abstract: We report on a rotaxane‐like architecture secured by the in situ tying of an overhand knot in the tris(2, 6‐pyridyldicarboxamide) region of the axle through complexation with a lanthanide ion (Lu 3+ ). The increase in steric bulk caused by the knotting locks a crown ether onto the thread. Removal of the lutetium ion unties the knot, and when the axle binding site for the ring is deactivated, the macrocycle spontaneously dethreads. When the binding interaction is switched on again, the crown ether rethreads over the 10 nm length of the untangled strand. The overhand knot can be retied, relocking the threaded structure, by once again adding lutetium ions. Abstract : Tying up loose ends : The use of a synthetic molecular knot to perform a mechanical function at the nanoscale is reported. A macrocycle is locked onto an axle by tying one end of the strand into an overhand knot. Untying the stopper knot leads to dethreading.